Sulfonamides in Tomato from Commercial Greenhouses Irrigated with Reclaimed Wastewater: Uptake, Translocation and Food Safety - Raquel Camacho-Arévalo; Carlos García-Delgado; Begoña Mayans; Rafael Antón-Herrero; Jaime Cuevas; María Luz Segura; Enrique Eymar (Agronomy, 2021)
The presence of antibiotics in crops is mainly caused by their irrigation with reclaimed wastewater and by the use of organic amendments of animal origin. During this work, the fate of sulfonamide antibiotics in tomato crop has been assessed in two commercial greenhouses located in Almería (Spain) irrigated with reclaimed wastewater. Samplings were made annually for two years. Sulfonamides in several parts of the plant (roots, leaves and fruits) as well as reclaimed wastewater, amendments and soils were analyzed by UHPLC-MS/MS. The results showed that sulfonamides accumulated in soils (sulfamethoxazole between 2 and 14 µg kg−1; sulfadiazine, sulfathiazole, sulfapyridine, sulfamerazine and sulfadimethoxine in concentrations below 1 µg kg−1) were in the reclaimed wastewater at concentrations in the ng L−1 range. Their distribution in plants depended on the sulfonamide. The sulfonamides detected in tomato were sulfadiazine, sulfapyridine, sulfamethazole, sulfamethoxazole and sulfadimethoxine. Sulfamethoxazole was the antibiotic with highest concentration in tomato fruit, exceeding 30 µg kg−1. All sulfonamides were below the Acceptable Daily Intake, however, further studies and legislation are needed to assure food safety.